OFR-37-94 Case Studies Of Submarine Tailings Disposal: Volume II -Worldwide Case Histories And Screening Criteria - [Further Case Histories; Screening Criteria] - Derek Ellis (The National Institute for Occupational Safety and Health (NIOSH), 1994)
Volume II of this two-part series on Submarine Tailings Disposal (STD) as a tailings management option for coastal and island mines contains descriptions of lesser known case histories. The Misima gold mine (Papua New Guinea) and the Black Angel lead-zinc mine (Greenland) are described in some detail as the best documented cases. Atlas copper mine (The Philippines) is less fully described due to relative lack of documentation. The Misima and Atlas STD systems are working to their design criteria. At Black Angel the system adopted did not prevent contamination for a number of reasons, which are now understood. Two cases are described where STD is being developed. They are the Cayeli Bakir copper mine Turkey), and the Toquepala and Cuajone mines (Peru). There is excellent documentation available for both cases. Three case histories are described where tailings have reached the sea either through beach or river discharge. In one case the STD option has been explored (Marcopper Mine, The Philippines). In the others we explore in hindsight whether STD might have been a viable alternative using the Screening Criteria that this Volume develops - see below. The mines are Bougainville Copper Mine in Papua New Guinea, and Jordan River Mine (Canada). There is potential for STD at all three sites. Finally, the Volume presents Screening Criteria for appraising STD, based on the experience in design, operation and environmental impact reviewed in the case histories.